Endocrine disruptors-arsenic, cadmium and lead in pre and postmenopausal black women with breast cancer (2017)
Background: The involvement of toxic metals in adiposity has been suggested to be contributory to the high incidence of breast cancer, particularly in sub-Saharan Africa. This study is aimed at evaluating serum arsenic, cadmium and lead in relation to adiposity and blood pressure in Nigerian women with breast cancer. Methodology: The study comprised 85 women newly diagnosed with breast cancer pre-therapy (cases) matched with 84 apparently healthy women without breast cancer (controls) according to age and menstrual phase. Arsenic (As), cadmium (Cd) and Lead (Pb) levels were determined by atomic absorption spectrophotometry. Blood pressure and anthropometry were determined by standard methods. Data analysed by Student’s t-test and Pearson correlation coefficient were considered statistically significant at p<0.05. Results: Cd and Pb levels were significantly higher in cases, compared with controls (p<0.05). Waist circumference (WC), hip circumference (HC), weight, height, waist hip ratio (WHR), waist height ratio (WHtR) were significantly higher in cases compared with controls (p<0.05). Cadmium positively correlated with diastolic blood pressure while FT4 inversely correlated with arsenic in the cases (p<0.05). Conclusion: Observations in this study suggest the involvement of these toxic metals in adiposity which could be involved in breast carcinogenesis.